Role of the Judiciary in Shaping Policy and Upholding the Rule of Law in Nigeria: Challenges and Prospects - ALOZIE, Christian Iheanyi (Socialscientia: Journal of Social Sciences and Humanities, 2025)
The judiciary is a fundamental institution in democratic governance, playing a critical role in upholding the rule of law, shaping public policy, and ensuring accountability in Nigeria’s multifaceted political and socio-economic landscape. This article explores the judiciary’s contributions to policy-making through judicial review, advancing social justice, addressing legislative gaps, and fostering public interest litigation. Landmark rulings have demonstrated its capacity to influence governance, safeguard constitutional principles, and mediate power dynamics among the executive, legislature, and citizenry. However, the judiciary’s effectiveness is constrained by significant challenges, including executive interference, corruption, capacity constraints, and a pervasive trust deficit. Judicial independence, though enshrined in Nigeria’s Constitution, is frequently undermined by political interference and the lack of financial autonomy, weakening its ability to deliver impartial justice. Corruption further erodes public trust, while insufficient infrastructure, inadequate training, and systemic inefficiencies hinder judicial performance, particularly in addressing complex policy issues. Despite these obstacles, the judiciary remains a critical player in driving societal reforms and ensuring governance aligns with constitutional ideals. This article highlights actionable recommendations to enhance judicial effectiveness, including securing financial and administrative autonomy, improving transparency through technology-driven reforms, strengthening ethical oversight, and building capacity through targeted investments in training and infrastructure. Additionally, legislative harmonization and civic engagement are essential to restore public trust and ensure judicial rulings have a lasting impact on governance. Addressing these systemic issues will enable the judiciary to fulfill its constitutional mandate more effectively, reinforcing its role as a cornerstone of Nigeria’s democratic development.